Efficacy of Flunixin meglumine in the amelioration of lameness in an Amphotericin B induced transient synovitis arthritis model in dairy steers - Schulz, Kara Lee (Kansas State University, 2010)
Lameness in cattle is a common cause of pain however there are no approved cattle analgesic drugs. Flunixin meglumine, the only non-steroidal anti-inflammatory drug approved for use in adult dairy cattle, is labeled for pyrexia associated with bovine respiratory disease, endotoxemia, acute mastitis and associated inflammation. There is currently a lack of objective data regarding the analgesic efficacy of flunixin meglumine in cattle. The objectives of this study were to characterize an amphotericin B-induced lameness model and to ascertain the analgesic effects of flunixin meglumine using multimodal assessment. We hypothesized that flunixin meglumine would provide analgesia as evidenced by increased activity levels as well as increased exerted force and contact area on the affected limb in flunixin treated steers. Amphotericin B-induced synovitis arthritis was induced in the distal interphalangeal joint of 10 dairy steers. The cattle were randomly allocated between a treatment and a control group. The treatment steers received flunixin meglumine at the time of arthritis induction and at 12 hours post-induction. Accelerometric, gait, pressure mat, vital parameter and plasma cortisol data were gathered in the pre and post-induction phases. The data were analyzed using linear mixed models with treatment and time designated as fixed effects. Induction of amphotericin B arthritis produced a moderate, transient lameness. Control steers were more than twice as likely to be lame as flunixin meglumine treated steers using visual lameness assessment (92.2% ± 8.1 versus 40.7% ± 2.5) (P<0.03). Flunixin meglumine treated steers placed significantly greater force and contact area on the affected foot. Control steers also placed significantly greater force, impulse and contact area on the paired claw as compared to control steers. Flunixin treated steers spent considerably less time in recumbency than their control counterparts, particularly in the immediate post-induction time period. This is one of the first studies to document the character of an amphotericin B-induced synovitis arthritis model in cattle as well as to document analgesic efficacy of a nonsteroidal anti-inflammatory drug in an induced lameness model. Flunixin meglumine was efficacious in providing analgesia in an amphotericin B-induced lameness model in dairy steers.
Keywords: lameness; bovine; analgesia; Biology, Veterinary Science (0778)